(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Hemorrhagic vasculitis (Henoch–Schönlein purpura, IgA vasculitis) is a common immune-inflammatory disease in children, affecting the skin, joints, gastrointestinal tract, and kidneys. The clinical heterogeneity and severity of the disease determine the prognosis and treatment strategy. Traditional laboratory tests- urinalysis, C-reactive protein, ESR assist in assessing disease activity, but their ability to detect severe forms early is limited. Modern laboratory biomarkers play a key role in early diagnosis, identification of severe forms, and prediction of renal complications. A comprehensive clinical and laboratory approach enables timely diagnosis of hemorrhagic vasculitis in children, prevents the progression of severe forms, and reduces the risk of long-term complications.